Endoscopic examinations and nursing care for patients in endoscopy unit - Bambrowicz, Jolanta; Cierzniakowska, Katarzyna; Szewczyk, Maria T.; Popow, Aleksandra; Banaszkiewicz, Zbigniew; Jawień, Arkadiusz (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Endoscopy today is commonly available and low risk procedure providing not only a visual diagnosis but also granting the opportunity for therapeutic maneuvers or visual check up following the treatment for GI tract disorders. Position of qualified endoscopic assistant nurse among other health care professionals composing the endoscopic team is not to be overestimated for her/his unique knowledge and skills. Thus nurse assistant co- ordinates the endoscopy unit activities such as taking care for patients pre- and post – procedurally, from one hand and participates in endoscopic examination and/or treatment, from the other. In this paper the indications that call for endoscopy are described as well as entirety of nursing and therapeutic activities in endoscopy unit.